Does Financial Literacy Matter? The Mediating Role of Financial Inclusion in Shaping Students’ Financial Management Behavior - Sumantri; Albetris; Muhammad Akbar (Global Research Collaboration, 2025)
This study aims to examine the effect of financial literacy on financial management behavior, with financial inclusion acting as a mediating variable among university students. Using a quantitative approach, data were collected through a structured questionnaire distributed to undergraduate students of the Management Department at the Graha Karya Muara Bulian University, covering cohorts from 2020 to 2025. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial literacy does not have a significant direct effect on financial management behavior. However, financial literacy has a positive and significant effect on financial inclusion, and financial inclusion, in turn, significantly influences financial management behavior. Furthermore, the mediation analysis reveals that financial inclusion fully mediates the relationship between financial literacy and financial management behavior. These findings suggest that financial knowledge alone is insufficient to shape sound financial behavior without adequate access to financial services. Therefore, improving financial inclusion is essential to enhance the effectiveness of financial literacy in promoting better financial management behavior, particularly among students.